Circulating markers of cellular immune activation in prediagnostic blood sample and lung cancer risk in the Lung Cancer Cohort Consortium (LC3). Issue 9 (22nd July 2019) - Huang, Joyce Y.; Larose, Tricia L.; Luu, Hung N.; Wang, Renwei; Fanidi, Anouar; Alcala, Karine; Stevens, Victoria L.; Weinstein, Stephanie J.; Albanes, Demetrius; Caporaso, Neil E.; Purdue, Mark P.; Ziegler, Regina G.; et al.
Abstract : Cell‐mediated immune suppression may play an important role in lung carcinogenesis. We investigated the associations for circulating levels of tryptophan, kynurenine, kynurenine:tryptophan ratio (KTR), quinolinic acid (QA) and neopterin as markers of immune regulation and inflammation with lung cancer risk in 5, 364 smoking‐matched case–control pairs from 20 prospective cohorts included in the international Lung Cancer Cohort Consortium. All biomarkers were quantified by mass spectrometry‐based methods in serum/plasma samples collected on average 6 years before lung cancer diagnosis. Odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer associated with individual biomarkers were calculated using conditional logistic regression with adjustment for circulating cotinine. Compared to the lowest quintile, the highest quintiles of kynurenine, KTR, QA and neopterin were associated with a 20–30% higher risk, and tryptophan with a 15% lower risk of lung cancer (all p trend < 0.05). The strongest associations were seen for current smokers, where the adjusted ORs (95% CIs) of lung cancer for the highest quintile of KTR, QA and neopterin were 1.42 (1.15–1.75), 1.42 (1.14–1.76) and 1.45 (1.13–1.86), respectively. A stronger association was also seen for KTR and QA with risk of lung squamous cell carcinoma followed by adenocarcinoma, and for lung cancer diagnosed within the first 2 years after blood draw. This study demonstrated that components of the tryptophan–kynurenine pathway with immunomodulatory effects are associated with risk of lung cancer overall, especially for current smokers. Further research is needed to evaluate the role of these biomarkers in lung carcinogenesis and progression. Abstract : What's new? The kynurenine pathway, by which tryptophan is degraded and NAD+ is synthesized, plays a role in inflammation and immune response. It may also be involved in cancer development and progression. Here, the authors investigated the relationship between the metabolites of the kynurenine pathway and risk of lung cancer. They found that lower levels of tryptophan and higher levels of kynurenine and quinolinic acid were associated with increased risk of lung cancer, especially in smokers. These biomarkers may be signs that immune suppression in the tumor microenvironment may boost cancer progression.